Matrix-Assisted Catalytic Printing for the Fabrication of Multiscale, Flexible, Foldable, and Stretchable Metal Conductors - Guo, Ruisheng; Yu, You; Xie, Zhuang; Liu, Xuqing; Zhou, Xuechang; Gao, Yufan; Liu, Zhilu; Zhou, Feng; Yang, Yong; Zheng, Zijian (Advanced materials (Weinheim), 2013)
Matrix‐assisted catalytic printing (MACP) is developed as a low‐cost and versatile printing method for the fabrication of multiscale metal conductors on a wide variety of plastic, elastomeric, and textile substrates. Highly conductive Cu interconnects (2.0 × 108 S/m) fabricated by MACP at room temperature display excellent flexibility, foldability, and stretchability.